Experimental Investigation of the Structural Performance of Concrete Containing Cellulose Fibers and the Anti-corrosive Effect of Green Corrosion Inhibitors - Ramshankar, Pushpanathan; Ganeshan, Pushpanathan; Raja, Kandhasamy; NagarajaGanesh, Balasubramanian (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This research was aimed to find the structural behaviour of "Calotropis procera" fibres added concrete and the effect of "Azadirachta indica" leaf slurry blended to concrete and exposed to seawater. Conventional and fibre reinforced concrete samples fabricated keeping the curing time as 7, 14 and 28 dayswere subjected to compression, split tensile, rebound hammer and ultrasonic pulse velocity test. Increase in curing time increased the structural properties and "Calotropis procerafibres" added samples produced respectively 19.5%, 15%, 10.3 and 14.5% improvement in the compression, tensile, rebound hammer and ultrasonic pulse velocity values.
Keywords: Calotropis procera fibres; fibre reinforced concrete; structural properties; accelerated corrosion test; green corrosion inhibitors